Large microlensing history and perspectives - Byalko, A. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The resent observational confirmation [1,2] of microlensing (i.e. gravitational focusing of light from a distant star by a small invisible body) becomes a scientific event of rather unusual appearance: this phenomena was theoretically predicted by Einstein 60 years ago [3], its observational probabilities were analyzed by me [4] and later by Paczynski [5]. Being finally observed the phenomena reveals difficulties to become a valuable observational instrument [6]. Actually the instrumental capacity of microlensing and the information about lens bodies occur to be limited: observations of a single event cannot say definitely what are the mass and transverse velocity of the lensing body, and how far it is located - only the product of the mass and distance becomes an actual outcome of each microlensing observation. I will report the results of a statistical approach to brightness changes of distant objects resulting in multiple microlensing. The theoretical time-correlation function will be compared with that for quasars observations [7]. Finally another observational procedure will be briefly discussed: the brightness curve of a pulsar in the radio waverange can reveal a diffraction pattern which could give information on both mass and distance to the lensing object.